Comprehensive Seismic Zonation Schemes for Regions at Different Scales - Sitharam, T. G. (Springer International Publishing, 2018)
This book reviews and assesses various methodologies for site characterization and site effects estimation to carry out seismic zonation at micro and macro levels. Readers will learn about the suitability of these methodologies for different levels of zoning in order to optimize the resources for carrying out seismic zonation. The Indian sub-continent is highly vulnerable to earthquake hazards, and past studies have focused primarily on the Himalayan region (inter-plate zone) and the northeast region (subduction zone). This book improves understanding of the seismicity in Peninsular India, which also has witnessed earthquakes of sizeable magnitude. Particular attention is given to the various methodologies for assessing seismic hazards, the scales at which site characterizations are carried out, and optimal methods for zonation practices using site data and hazard indexes. This book will be of use to post-graduates and doctoral students researching seismic zonation, hazard assessment and mitigation, and spatial data in earth sciences.